2011
DOI: 10.1539/joh.l10108
|View full text |Cite
|
Sign up to set email alerts
|

Acute Arsine Poisoning Confirmed by Speciation Analysis of Arsenic Compounds in the Plasma and Urine by HPLC‐ICP‐MS

Abstract: Acute Arsine Poisoning Confirmed by Speciation Analysis of Arsenic Compounds in the Plasma and Urine by HPLC-ICP-MS: YukihiroYoshimura, et al. Department of Infectious Disease, Yokohama Municipal Citizen's Hospital-Objectives: Arsine, a potent hemolytic agent, is widely used in the semiconductor industry. We report a case of arsine poisoning confirmed by arsenic speciation analysis in serum and urine that occurred in a recycling factory. Case: A male worker in his twenties noticed hematuria 3 h after finishing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In a study on a population of west Bengal of India exposure to different levels of arsenic, serum bilirubin was elevated in total exposed individuals but no significance was detected in dose-response tests [ 56 ]. ALT activity in plasma were frequently elevated after arsenic exposure in human [ 56 , 57 ] or animal models [ 58 , 59 ]; however, such changes are usually significant only under very high concentrations [ 57 , 60 ] or prolonged exposure of weeks to months[ 61 – 63 ]. Thus, the arsenate exposure in this study was probably not sufficient to induce severe liver damages.…”
Section: Resultsmentioning
confidence: 99%
“…In a study on a population of west Bengal of India exposure to different levels of arsenic, serum bilirubin was elevated in total exposed individuals but no significance was detected in dose-response tests [ 56 ]. ALT activity in plasma were frequently elevated after arsenic exposure in human [ 56 , 57 ] or animal models [ 58 , 59 ]; however, such changes are usually significant only under very high concentrations [ 57 , 60 ] or prolonged exposure of weeks to months[ 61 – 63 ]. Thus, the arsenate exposure in this study was probably not sufficient to induce severe liver damages.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, human metabolites in urine and blood after inhalation of arsine (Apostoli et al, 1997, Yoshimura et al, 2011 are the same as the metabolites found in inorganic arsenic exposure. Thus, the effects of inorganic arsenic toxicity should be considered in chronic arsine exposure.…”
Section: Respiratormentioning
confidence: 64%
“…Finally, it is now very uncommon for this review to report on cases of acute occupational metal intoxication. Yoshimura et al 132 confirmed a case of acute arsine poisoning in a worker from a semiconductor recycling plant. Urine and serum As species were determined using HPLC-ICP-MS. On admission, serum total As was 244.8 mg L À1 , which declined over the five days of hospitalisation to 97.1 mg L À1 .…”
Section: Arsenicmentioning
confidence: 91%